Pertanggungjawaban Pidana terhadap Pelaku Kekerasan Penganjuran Organisasi Kemasyarakatan - I Wayan Ajus Sentana Putra Putra; I Made Sepud Sepud; Anak Agung Sagung Dewi (Jurnal Preferensi Hukum, 2020)
The increasing number of new organizations appearing as a result of the freedom of expression, association and assembly, triggers the expression of dissent. It manifests aspects of democracy in the life of the nation and state. Freedom of association followed by anarchist actions taken by several organizations serves as a real answer due to the existence of legal mechanisms that do not work well. So, rather than not working, the organization is better to take action by walking alone. Such behavior is unconsciously an act against the law. The problem examined in this study relates to the regulation of criminal acts advocating social organizations and criminal liability against perpetrators of violence in the advocacy of such social organizations. This type of research is normative legal research with a statutory approach. Analysis of legal material is done by descriptive method. The regulation of criminal acts advocating social organizations set forth in Articles 55 and 56 of the Criminal Code. The form of offense or the element of inclusion in article 5 of the Criminal Law Code consists of four types of offenses, including: pleger, doenpleger, uitlokker and mediepleger. The criminal liability of perpetrators of violent acts advocated by social organizations is manifested in a rule requiring the makers and perpetrators to be equally punished; however, supporters can be sentenced lighter than the maker, which is reduced by one third of the maximum criminal offense threatened with capital punishment or life imprisonment, the assistant is sentenced to a maximum of 15 years in prison